2015
DOI: 10.1007/s00415-015-7795-3
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking controlled cognitive function tests in patients with amyotrophic lateral sclerosis: a controlled proof-of-principle study

Abstract: Amyotrophic lateral sclerosis (ALS) primarily affects motor and speech abilities. In addition, cognitive functions are impaired in a subset of patients. There is a need to establish an eye movement-based method of neuropsychological assessment suitable for severely physically impaired patients with ALS. Forty-eight ALS patients and thirty-two healthy controls matched for age, sex and education performed a hand and speech motor-free version of the Raven's coloured progressive matrices (CPM) and the D2-test whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
(49 reference statements)
3
24
0
Order By: Relevance
“…This study shows the feasibility and reliability of a mobile eye-tracking screening tool based on the ECAS which can be easily administered even at the patient's bedside in a time frame of usually less than one hour. As in previous studies with healthy subjects (15,24,25) and ALS patients (16), there was a strong association between performance in both modalities of cognitive testing (oculomotor and paper-and-pencil) with satisfying correlations between scores in all relevant domains of both versions of the ECAS in the healthy control and in the patient sample.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study shows the feasibility and reliability of a mobile eye-tracking screening tool based on the ECAS which can be easily administered even at the patient's bedside in a time frame of usually less than one hour. As in previous studies with healthy subjects (15,24,25) and ALS patients (16), there was a strong association between performance in both modalities of cognitive testing (oculomotor and paper-and-pencil) with satisfying correlations between scores in all relevant domains of both versions of the ECAS in the healthy control and in the patient sample.…”
Section: Discussionsupporting
confidence: 82%
“…A pseudo-randomized study design similar to the one previously reported by Keller et al. 2015 (16) was used: To avoid sequence effects, patients and HC were each subdivided into two age-gender-and education-matched groups. One group completed the German paper-and-pencil ECAS version (23) according to standard procedures first, followed by the eye-tracking based version, whereas the other group did vice versa.…”
Section: Designmentioning
confidence: 99%
“…This study shows the feasibility and reliability of a mobile eye-tracking screening tool based on the ECAS which can be easily administered even at the patient's bedside in a time frame of usually less than one hour. As in previous studies with healthy subjects (15,24,25) and ALS patients (16), there was a strong association between performance in both modalities of cognitive testing (oculomotor and paper-andpencil) with satisfying correlations between scores in all relevant domains of both versions of the ECAS in the healthy control and in the patient sample.…”
Section: Discussionsupporting
confidence: 82%
“…Even though oculomotor impairments may occur in some patients in the course of ALS (12)(13)(14), for many patients it still has the potential to be a valuable tool in the detection of cognitive deficits. Previous studies have already proven the applicability of this approach for ALS patients (15)(16)(17)(18), using different tasks of executive functioning and devices which require a stationary testing environment. Yet, a mobile version of a cognitive screening tool specifically designed for bedside use in ALS patients is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Keller et al [15] developed a neuropsychological assessment method for patients with Amyotrophic lateral sclerosis (ALS) based on eye movement. The participants (forty-eight ALS patients and thirty-two healthy controls) were tested by two tests (D2-test and Raven's coloured progressive matrices) adapted for eyetracking control.…”
Section: Related Workmentioning
confidence: 99%